Methods of teaching centered on learning and formative assessment in higher education - Sá, Susana Emília Vaz Oliveira (2018)
We analyse the importance of meaningful learning and the use of a formative assessment strategy, promoted by peer learning methods centred on the students, in a curricular unit (CU) pertaining to a degree in Exact Sciences, in a Higher Education Institution. Five students from the CU were questioned, through a focus group; the teacher was interviewed. Data of 12 hours of lessons was analysed and categorised using webQDA. We conclude that emphasising the students’ engagement in teaching, learning, and evaluation, has the power to drive the methodological teaching options to incline towards active methods that involve students in activities that foster meaningful learning. And the use of systematic formative assessments, integrated in the teaching-learning process, by using effective feedback, is most likely to make students and teachers responsible for an overall improvement in learning.